Differences of the Fertility Potential between Buffaloes (Bubalus bubalis) and Cattle (Bos indicus): The Role of Antimullerian Hormone (AMH) - Berdugo-Gutiérrez, Jesus A.; Echeverri, Jose Julían; Tarazona, Ariel Marcel; Herrera, Albeiro López- (Journal of Buffalo Science, 2018)
For years the study of the differences in reproduction between bovines have been restricted to describe the consequences not the causes, it is very easy to find differences in parameters such as embryo/oocyte morphology, metabolism, cleavage rate, but it is quite difficult to find papers trying to explain the reason of this differences and it is not possible to identify their influence in the reproductive parameters and answer to reproductive biotechnologies. The idea that the quantity of follicles and oocytes in ovaries impacts on fertility is a long-held tenet in reproductive biology (46), Follicle formation occurs during fetal life in ruminants and primates. The establishment of the pool of primordial follicles is critical to a female’s reproductive success, but very little is known about how this important developmental process is regulated. It has been reported is has been reported in buffaloes the effect of season in the gene expression of oocytes and follicles (47) .However, until now very few studies has been attempted to evaluate this fundamental hypothesis, it is possible to think that animals with low follicle count such buffaloes has lower fertility than cattle but this must be demonstrated. The aim of this review is to present evidence related to the differences in reproductive potential in two closely related bovines: buffaloes (Bubalus bubalis) and cattle (Bos taurus and Bos indicus), with special emphasis in the role of antimullerian hormone (AMH) and discuss their possible role in the application of reproductive biotechnologies.